THE CAREERS OF THE EDUCATION IN TECHNOLOGY GRADUATES - Noga, Henryk (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
A very important indicator of the usefulness of studies is the graduates’ career advancement. It indicates to what extent studies facilitate or speed up the professional career. The research concerned the careers of Education in Technology graduates and their professional adaptation. An attempt to assessment the quality of education has also been made. After graduation students are able to assess the quality of education and its impact on their lives and professional careers.